1991
DOI: 10.1111/j.1469-8137.1991.tb00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of air pollution and water stress on leaf blight and twig cankers of London planes [Platanus×acerifolia (Ait.) Willd.] caused by Apiognomonia veneta (Sacc. & Speg.) Höhn.

Abstract: summary Potted 2‐year‐old cuttings of London plane trees [Platanus×acerifolia (Ait.) Willd.] were raised under well‐watered (WW) or water stress (WS) conditions in two semi‐open‐top chambers and fumigated with ambient air (AA) and filtered air (FA). In the FA chamber, charcoal and Reox‐Purafil† filters removed 65–100% of O3, 50–90% of NOx, and 80–95 % of SO2. After leaf inoculations in spring with conidia of Apiognomonia veneta (Sacc. & Speg.) Höhn., significantly fewer and smaller lesions appeared on AA than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…This fact indicated that B pendula started and finished vegetation later in the polluted plots in comparison with the control. Our data are consistent with the results of other authors who showed a decrease in emergence rate from winter dormancy for other tree species upon exposure to environmental pollution ( Vonsury and Fluckiger 1991 ). In 2010 and 2013, the dose–response dependences of the fallen leaves were hormesis and paradoxical effect, accordingly ( Figure 6a and d ).…”
Section: Resultssupporting
confidence: 93%
“…This fact indicated that B pendula started and finished vegetation later in the polluted plots in comparison with the control. Our data are consistent with the results of other authors who showed a decrease in emergence rate from winter dormancy for other tree species upon exposure to environmental pollution ( Vonsury and Fluckiger 1991 ). In 2010 and 2013, the dose–response dependences of the fallen leaves were hormesis and paradoxical effect, accordingly ( Figure 6a and d ).…”
Section: Resultssupporting
confidence: 93%
“…A further reason for mixed responses to drought in anthracnose diseases is that different organs are affected. Differential effects of a water stress treatment were demonstrated on London plane (Platanus acerifolia) cuttings when leaf or twig symptoms were considered, with a negative effect for the former and a positive for the latter [188]. The same was observed for Septoria musiva [130].…”
Section: Disease-or Health Status-related Variablesmentioning
confidence: 48%